Sex-differences in elite-performance track and field competition from 1983 to 2015 - Ospina Betancurt, J.; Zakynthinaki, M. S.; Martines-Patiño, M. J.; Cordente Martinez, C.; Rodriguez Fernández, C. (Journal of Sports Sciences, 2018)
The purpose of this study was to assess the veracity of the Court of Arbitration for Sport`s assertion that sex-differences in athletic performance in elite-standard track and field competition is of the order of 10-12%. Exponential curves were fitted to the data of selected track and field events of the finals of all IAAF World Championships and Olympic Games from 1983 to 2016. For each curve, the coefficient of determination R2 was calculated, in combination the corresponding 95% confidence intervals for the curve constants. Sex-differences were evaluated via differences in the fitted curves between men and women. Mean performances of winners, as well as overall performance means of all participants, were also analyzed. The calculated sex-difference was 8.2 ± 1.0% - 11.8 ± 2.1% for sprints, 10.3 ± 3.3% - 12.8 ± 4.0% for middle and long-distance events, 9.7 ± 2.9% - 13.1 ± 2.9% for relays and 14.2 ± 2.2% - 25.0 ± 4.4% for jumps. This study therefore confirms that the percentage difference accepted by the CAS is appropriate for elite-standard track and field events.